فاعلية برنامج إرشادي في تنمية الوعي بالرعاية المقدمة من الأم لطفلها المعاق ذهنيا - السميط، حصة عبدالرحمن أحمد; الشايع، منيرة عبدالرحمن Alshayea, Munirah Abdulrahman; الخزي، منال عبدالله (جامعة المنيا - كلية التربية النوعية, 2022)
يهدف البحث إلى إعداد برنامج إرشادي في تنمية الوعي بالرعاية المقدمة من الأم لطفلها المعاق ذهنيا، وذلك من خلال كشف الفروق بين العاملات وغير العاملات، أمهات الذكور وأمهات الإناث، في مستوى الوعي عن الإعاقة الذهنية، تحديد أثر تطبيق البرنامج الإرشادي في تنمية الوعي لأمهات الأطفال المعاقين ذهنيا بطرق رعاية أطفالهن، ولتحقيق أهداف البحث أستخدم المنهج الوصفي التحليلي بجانب المنهج التجريبي، وتمثلت أدوات البحث في: استمارة البيانات العامة للأمهات واستبيان الرعاية المقدمة بجانب البرنامج الإرشادي المعد من قبل الباحثين لأمهات الأطفال المعاقين ذهنيا، وطبقت الدراسة على عينة قوامها (112) أم، وأسفرت نتائج الدراسة عن: وجود فروق دالة إحصائيا عند مستوى دلالة 0.01 في محور الرعاية النفسية والاجتماعية والفروق لصالح الأمهات غير العاملات، أيضا وجود فروق دالة إحصائيا بين الأمهات اللاتي لديهن خبرة سابقة في التعامل مع طفل معاق ومن لم يسبق لهن التعامل في محاور الاستبيان الثلاثة (الرعاية النفسية والاجتماعية-الرعاية الصحية وإكساب المهارات-الرعاية الغذائية)، توجد فروق ذات دلالة إحصائية بين عينة الدراسة في الاختبارين القبلي والبعدي لصالح الاختبار البعدي عند مستوى دلالة 0.001 ويثبت ذلك أن البرنامج الإرشادي في هذه الدراسة نجح في تحقيق الهدف منه، وقد أوصت الدراسة بضرورة عمل دورات إرشادية لأسر المعاقين ذهنيا وإرشادهم لطرق التعامل مع الإعاقة من خلال الجمعيات الأهلية والقوافل الصحية. The research aims to prepare an indicative program in developing awareness of the care provided by the mother to her mentally disabled child, by revealing the differences between working and non-working women, mothers of males and mothers of females, in the level of awareness about mental disability, determining the impact of the application of the counseling program in developing awareness for mothers of children with disabilities. Mentally, in ways of caring for their children, and to achieve the objectives of the research, the descriptive analytical approach was used in addition to the experimental method. The research tools were: the general data form for mothers and the questionnaire for the care provided alongside the counseling program prepared by researchers for mothers of mentally handicapped children, and the study was applied to a sample of (112) mothers, The results of the study resulted in: the presence of statistically significant differences at the level of significance 0.01 in the axis of psychological and social care and the differences in favor of non-working mothers, also the presence of statistically significant differences between mothers who had previous experience in dealing with a disabled child and those who had not previously dealt with the three questionnaire axes (Psychological and social care-health care and skills acquisition-nutritional care), there are statistically significant differences between the study sample in the test Aren the tribal and the post-test in favor of the post-test at a significance level of 0.001, and this proves that the counseling program in this study succeeded in achieving its goal
Keywords: الإرشاد النفسي -- الاضطرابات السلوكية -- الأطفال المعوقين -- الإعاقة الذهنية -- الرعاية الأسرية